Single stage posterior instrumentation and anterior interbody fusion for tuberculosis of dorsal and lumbar spines - Pandey, BK; Sangondimath, GM; Chhabra, HS (Nepal Orthopaedic Association Journal, 2013)
Background: Spine is the most common site for osseous involvement of tuberculosis, accounting around 50% cases of musculoskeletal tuberculosis. The most frequent sites of the involvement are the thoracic and lumbar spine. The anterior column is primarily affected resulting in progressive or residual kyphotic deformity even after the eradication of the disease by chemotherapy. Various surgical techniques like anterior fusion, posterior or combined fusion have been described. In this study we evaluated the clinical outcome and radiological results of single stage posterior instrumentation and anterior interbody fusion for tuberculosis of dorsal and lumbar spine. Methods: Details of the patients of tuberculosis of dorsal and lumbar spine operated with single stage posterior instrumentation and anterior interbody fusion from December 2004 to June 2008 were retrieved from the hospital database. There were 55 cases operated with this technique. Thirty patients, whose final details were available, were involved in this study. Pre-operative, post-operative and final follow up clinical and radiological assessments were performed. The follow up ranged from 18 to 60 months. Results: Average operation time was 5 hours 45 minutes and blood loss was 1100 ml. Anterior body fusion was achieved in all the patients. 93.3% of the patients had neurological improvement. Satisfactory post-operative kyphotic angle correction was achieved. There was minimal final loss of kyphotic correction. One patient had post-operative wound infection. Post operative paralytic ileus, chest infection, urinary tract infection, jaundice were the complications found in the patients. No graft related complication was seen. There was no recurrence of the disease in any of the cases. Conclusion: Single stage anterior debridement and interbody fusion with posterior instrumentation can be performed safely to achieve satisfactory clinical and radiographic outcomes in patients of thoracic and lumbar tuberculosis. DOI: http://dx.doi.org/10.3126/noaj.v2i1.8136 Nepal Orthopaedic Association Journal Vol.2(1) 2011: 21-26